Third-Party Entity Voltage Regulation Ancillary Service Compensation and Procurement in Distribution Networks with High-Penetration PV - Jing BAI; Guanghou JIN; Helin SUN; Chufan HU; Jinquan ZHAO; Tianhua CHEN (Zhongguo dianli)
The large-scale grid connection of distributed photovoltaics brings many voltage problems. Demand responses can bring flexible voltage regulation ability to solve problem of photovoltaics curtailments. Under the background of building the new type power market mechanism, a strategy for third-party entity voltage regulation ancillary service procurement in distribution networks with high-penetration PV is proposed. Based on the analysis of the compensation range of third-party entity, the computation method of the compensation mechanism of third-party entity voltage regulation ancillary service is discussed. For the scenario of high penetration PV induced voltage regulation difficulty, we suggest the photovoltaic power generation companies share the compensations of voltage regulation ancillary service. Considering fully regulation ability of grid side reactive power equipment, an optimization model for third-party entity voltage regulation ancillary service procurement in distribution networks is established, which the goal is to minimize the costs of photovoltaics curtailment and the compensations of voltage regulation ancillary service. An example shows that the strategy proposed in this paper can maintain the safe operation of the distribution network while taking into account the benefits of the photovoltaic power companies and the third-party entities, and achieve a win-win situation for all parties.